Manufacturing and Testing Pneumatic Pads Adjustable Socket for A Below-Knee Prosthetic - Kubba, Ammar Issam Salih; Alammar, Ahmed A. (Al-Nahrain Journal for Engineering Sciences, 2024)
The purpose of this research is to manufacture and test adjustable sockets for below-knee amputation. This article studies using the pnuematic–pads for adjustable sockets. The manufacturing of an adjustable socket with pneumatic pads goes through several stages: In the theoretical design of the adjustable socket, the suggested materials were studied for the pneumatic pads, tubes, and pneumatic pump which should be suitable for the suggested application. In the experimental work, using composite materials for manufacturing the socket consisting of perlon and resin to achieve the rigid shape and required flexibility for the prosthetic user with the pneumatic pads. After assembling the adjustable socket parts, the pneumatic pads, the pump and the tubes, the socket were tested for several times on the patient. In the last stage, the pressure between the socket and the residual limb was measured using F-socket, and it was found that the results were: anterior (160kPa), lateral (167kPa), posterior (153kPa) and medial (348kPa). By comparing these results with what was previously studied, the pressure between the socket and the residual limb is within the acceptable range. The design provides good suspension and more adaptability to the change in stump volume. A posative feedback was given by the patient who used the prosthetic patient for several days as a trial to measure its safety and comfortablty.